Do sanctions affect the environment? The role of trade integration - Khalid, U.; Ali, Muhammad Tahir; Okafor, L.; Sanusi, O. I. (Elsevier, 2024)
Environmental degradation is one of the potentially unforeseen consequences of sanctions, yet few studies have investigated how sanctions affect the environment. For instance, by restricting the acquisition of more efficient technologies, sanctions can strain natural resources and erode environmental performance. Therefore, this study investigates the moderating effects of trade integration on the underlying links between several types of sanctions (i.e., military, arms, trade, financial, and travel) and the environmental quality of the target country. A rich dyadic dataset consisting of 214 sender countries/states, 135 target countries/states, and 28,532 country pairs is used for the empirical analysis. A multi-way panel fixed effects model is employed for the empirical analysis. This approach allows us to control for the unobserved sender and target country-specific as well as time-specific characteristics that might affect environmental performance. The results show that most sanctions result in the deterioration of the environmental quality. In contrast, trade sanctions promote the environmental quality of the target country. We also find that sanctions adversely impact the ecological aspect of the environment while positively influencing the climate change aspect of environmental quality. The results also show that greater bilateral trade interdependence between the sender and the target country helps to mitigate the adverse impacts of most sanctions. The findings of this study suggest that the real effects of sanctions on environmental quality cannot be empirically disentangled if several types of sanctions are clubbed under the umbrella of ‘sanctions’ and captured using a single dummy variable, as is often done in the extant literature. Policies that encourage greater economic integration, such as trade liberalization with multiple countries, can be used strategically by a country to reduce threats of being sanctioned or vulnerabilities to the negative effects of sanctions on the environment.